PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA YAYASAN BAITUS SA’ADAH AMANAH DEPOK JAWA BARAT - Maulidiya Putri; Chotamul Fajri (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine how "The Effect of Work Discipline and Work Motivation on Employee Performance at the Baitus Sa'adah Amanah Foundation in Depok, West Java". The method used is a quantitative method with an associative approach. The sampling technique used saturated sampling and obtained a sample in this study totaling 67 respondents. This research uses the help of SPSS version 26. Data analysis and test techniques include simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, dertemination coefficient analysis, validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, t test and F test. Based on the results of research work discipline has a positive and significant effect on employee performance with the regression equation Y = 28.110 + 0.338X1. Hypothesis testing obtained (tcount 2.943> ttable 1.997) and significance value (0.000 <0.05). The results of work motivation research have a positive and significant effect on employee performance with the regression equation Y = 13.779 + 0.682X2. Hypothesis testing obtained (tcount 7.838> ttable 1.997) and significance value (0.000 <0.05). Work Discipline and Work Motivation simultaneously have a positive and significant effect on employee performance with the regression equation Y = 12.686 + 0.47 X1 + 0.662 X2. Hypothesis testing obtained (Fcount 30.469> Ftable 3.14) and significance value (0.000 <0.05).